Description of the last instar larva and new contributions to the knowledge of the pupa of dasyhelea mediomunda Minaya (Diptera, Culicomorpha, Ceratopogonidae) - Diaz, Maria Florentina (2016)
The fourth instar larva of Dasyhelea mediomunda Minaya is described for the first time and a complete description of the pupa is provided, through use of phase-contrast microscope and scanning electron microscope. Studied specimens were collected in a pond connected to a small wetland "mallin" on the Patagonian steppe, Chubut province, Argentina.